How labor migrants fare - Constant Amelie; Zimmermann Klaus F (Berlin Springer-Verlag, 2004)
Using data from the United States, Canada, many European countries, Australia and New Zealand, the chapters study the developments of earnings, employment, unemployment, self-employment, occupational choices and educational attainment after migration. Th
Keywords: Immigrants(Labor economics)